Reworkable thermal visbreaking foam tape and preparation method thereof

By using a thermally detoxified pressure-sensitive adhesive prepared with acrylic polymer with an amine group and a carboxyl group in the side chain, the problem of the existing thermally detoxified tape reducing residual glue and viscosity at high temperature conditions is solved, and the thermally detoxified effect of efficient and recycled use is achieved.

CN119662151APending Publication Date: 2025-03-21SUZHOU SHIHUA NEW MATERIAL TECH

Patent Information

Application Number
CN202411895790.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing thermal adhesive tape is prone to residual glue under high temperature conditions, has reduced viscosity and cannot be recycled, and has a long baking time at high temperature, which can easily lead to problems in the pyrolytic glue process.

Method used

Acrylic polymers and liquid crystal polymers with side chains containing amine groups and carboxyl groups are used as the main components of the thermally detachable pressure-sensitive adhesive. They are prepared by radical polymerization, combined with polyisocyanate type and epoxy type curing agents to form high-viscosity pressure-sensitive adhesives, and achieve rapid detachment reduction and peeling at high temperatures.

Benefits of technology

High viscosity bonding at room temperature is achieved, and rapid adhesive reduction and peeling are reduced or peeled above 75°C. The heat-relieving pressure-sensitive adhesive after peeling can be recycled, and after the temperature returns to room temperature, the adhesive force can be restored, avoiding residual glue and degumming problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of pressure-sensitive adhesives, in particular to a reworkable thermal visbreaking foam adhesive tape and a preparation method thereof. The pressure-sensitive adhesive comprises a foam base material, the two sides of the base material are coated with a high-viscosity pressure-sensitive adhesive and a thermal-viscosity-reducing pressure-sensitive adhesive respectively, and release films are attached to the outer sides of the pressure-sensitive adhesive layers respectively. The invention provides the foam double-sided tape which is high in normal-temperature binding power, the binding power of a thermal viscosity reduction surface can be rapidly reduced when the foam double-sided tape is heated to a certain temperature or above, and the high-viscosity surface still keeps high binding power. After the temperature of the adhesive tape is recovered to normal temperature, the adhesive force of the thermal visbreaking surface can be recovered, and the problems that common adhesive tapes in the market cannot be recycled, the baking temperature is high, the balance time under the high-temperature condition is long, and adhesive residues are easily generated in the adhesive pyrolysis process are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesives, in particular to a reworkable heat-reducing adhesive foam tape and a preparation method thereof. Background Art

[0002] With the development of the electronic information industry, semiconductor components and electronic devices are becoming smaller, thinner and lighter. Pressure-sensitive adhesives are widely used in the bonding of electronic product components, screens, and frames to fix and protect them. However, when electronic components need to be repaired or reworked, the pressure-sensitive adhesive layer often needs to be removed manually or cut off with a knife, which can easily damage the product, leave residual adhesive, and complicate the operation process.

[0003] As a pressure-sensitive adhesive with adjustable peel strength, the viscosity of the pressure-sensitive adhesive can be quickly reduced by heating the pressure-sensitive adhesive to a certain temperature, so that electronic components, screens, frames, etc. can be easily separated from the adherends without damaging the products. Therefore, the research on the pressure-sensitive adhesive is a subject of great industrial value.

[0004] At present, there are products of this type on the market. For example, a Chinese patent with patent number CN201810107039.1 discloses a reworkable tape and a preparation method thereof. The reworkable tape comprises a first release material layer, a first heated de-viscosity adhesive layer and a second release material layer arranged in sequence. The heated de-viscosity adhesive used in the first heated de-viscosity adhesive layer comprises a solvent-based polyacrylate pressure-sensitive adhesive, a tackifying resin, foamed particles, a thermally conductive filler, a dispersant and a curing agent.

[0005] The reworkable adhesive tape prepared by the invention has strong adhesive force and can be automatically peeled off without leaving any residual adhesive after being heated at high temperature.

[0006] Another example is a Chinese patent with patent number CN202111069562.8, which discloses a thermal anti-viscosity film and its preparation method and application, belonging to the field of viscose film technology. The thermal anti-viscosity film of the present invention includes a substrate layer, a release film layer disposed on the substrate layer, and a heat-debonding adhesive layer disposed between the substrate layer and the release film layer. The raw material components and their mass parts of the heat-debonding adhesive layer are 100 parts of acrylic adhesive, 1-10 parts of resin, 2-10 parts of foamed microspheres, 0.1-2 parts of curing agent, and 30-60 parts of solvent.

[0007] The heat-reducing adhesive film prepared by the invention has good adhesion to objects of different materials, a low peeling force range, and good reworkability; the high peeling force range has good positioning and is not easy to warp.

[0008] However, including the above patented products, the existing heat-reducing adhesive tapes generally have the following problems: foaming of the adhesive layer under high temperature conditions will make the surface rough, reduce the adhesive layer's viscosity, and make it impossible to recycle; the baking temperature is high, the equilibrium time is long under high temperature conditions, and residual adhesive is easily generated during the thermal debonding process.

[0009] In order to solve the above problems, the present invention provides a reworkable heat-reducing viscosity-reducing foam tape and a preparation method thereof. Summary of the invention

[0010] The purpose of the present invention is to provide a foam double-sided adhesive tape with high adhesive force at room temperature, wherein the adhesive force of the heat-reduced adhesive surface decreases rapidly when heated above a certain temperature, while the high-adhesive surface still maintains high adhesive force. When the temperature of the adhesive tape returns to room temperature, the adhesive force of the heat-reduced adhesive surface can be restored.

[0011] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0012] A reworkable heat-reducing adhesive foam tape comprises a substrate, pressure-sensitive adhesive layers are coated on both sides of the substrate, a release film is attached to the outer side of the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer comprises a high-viscosity pressure-sensitive adhesive and a heat-reducing pressure-sensitive adhesive;

[0013] The heat-reducing pressure-sensitive adhesive is an acrylic polymer, including the following components by weight:

[0014] 100 parts of an acrylic acid polymer having an amine group and a carboxyl group in the side chain;

[0015] 10-30 parts of liquid crystal polymer;

[0016] Curing agent 0.3-1.2 parts;

[0017] 30-50 parts of solvent;

[0018] Acrylic polymer containing amino and carboxyl groups in the side chain, with a glass transition temperature Tg of -15 to -25°C, a viscosity of 10,000 to 15,000 cps / 25°C, and a weight average molecular weight M W 50000~200000, molecular weight distribution is 1.5~3.5;

[0019] The storage modulus G′ of acrylic polymer at 23°C is between 200 and 400 KPa, and the loss factor tanδ is between 1.0 and 2.0;

[0020] The storage modulus G' of the acrylic polymer at 75°C is between 15 and 30 KPa, and the loss factor tanδ is between 0.01 and 0.03.

[0021] More optimally, the acrylic polymer containing amine and carboxyl groups in the side chain includes the following weight components:

[0022] 20-30 parts of long alkyl acrylate monomer;

[0023] 30-40 parts of isooctyl acrylate monomer;

[0024] 15-20 parts of ethyl acrylate monomer;

[0025] 0.5-4 parts of hydroxyethyl methacrylate;

[0026] 1 to 6 parts of acrylic acid;

[0027] Thermal initiator 0.2-1.0 part;

[0028] 100-130 parts of solvent;

[0029] After the above substances are uniformly mixed, a free radical polymerization reaction is carried out at 60-90° C. by slowly dropping the mixed solution step by step for 6-8 hours to obtain an acrylic acid polymer having an amino group and a carboxyl group in the side chain.

[0030] More optimally, the long alkyl acrylate monomer is at least one of hexadecyl acrylate, octadecyl acrylate and behenyl acrylate; the thermal initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, lauroyl peroxide and tert-butyl perbenzoate.

[0031] More optimally, when preparing the liquid crystal polymer, 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoate, 2,6-di-tert-butyl-p-cresol, N,N-dicyclohexylcarbodiimide, dichloromethane, and 4-dimethylaminopyridine are reacted at room temperature for 24 hours;

[0032] After washing, filtering, rotary evaporation and recrystallization, a liquid crystal monomer, namely 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoate, is obtained;

[0033] Finally, the liquid crystal monomer is used to obtain a liquid crystal polymer under the irradiation of a photoinitiator and LED ultraviolet light.

[0034] More optimally, the solutions used in the washing process are 5wt% hydrochloric acid solution, 5wt% NaHCO3 solution, and saturated NaCl solution.

[0035] More optimally, the high viscosity pressure sensitive adhesive is an acrylic pressure sensitive adhesive, comprising the following weight components:

[0036] 100 parts of an acrylic polymer having an amine group in the side chain;

[0037] Curing agent 0.2-1 part;

[0038] 15-30 parts of solvent;

[0039] The glass transition temperature Tg of the acrylic pressure-sensitive adhesive is -25 to 5°C, the weight average molecular weight MW is 500,000 to 1,000,000, and the molecular weight distribution is 1.5 to 3.2;

[0040] The storage modulus G′ of acrylic pressure-sensitive adhesive at 23°C is 200-400 KPa, and the loss factor tanδ is 1.0-2.0;

[0041] The storage modulus G′ of acrylic pressure-sensitive adhesive at 75°C is between 60 and 90 KPa, and the loss factor tanδ is between 0.7 and 0.9.

[0042] More optimally, the curing agent is at least one of polyisocyanate, epoxy curing agent and metal salt curing agent; the substrate is at least one of polyurethane foam, polyethylene foam and polypropylene foam;

[0043] The thickness of the substrate is 0.05 to 0.5 mm;

[0044] The thickness of the pressure-sensitive adhesive layer on both sides of the substrate is 20 to 70 μm.

[0045] More optimally, the solvent is at least one of isopropanol, ethyl acetate, toluene and butanone.

[0046] More optimally, the thickness of the release film is 40-80 μm;

[0047] The release force of the light release surface is 8-15gf / in after 24h, and 20-30gf / in after aging at 70℃ for 20h, and the residual rate is ≥85%;

[0048] Release force of heavy release surface for 24h is 30~55gf / in, release force of aging at 70℃ for 20h is 35~70gf / in, residual rate ≥80%

[0049] The present invention also provides a method for preparing a reworkable heat-reducing viscosity foam tape, which is used to prepare any of the above-mentioned reworkable heat-reducing viscosity foam tapes, and the coating method used is one of micro-dimpled coating and comma blade coating;

[0050] The specific operation is as follows: the components of the heat-reducing pressure-sensitive adhesive and the high-viscosity pressure-sensitive adhesive are mixed to prepare a solution, and the dispersion speed is 400-500 rpm / min;

[0051] The solution is sequentially coated on both sides of the foam substrate, and after being dried, cured and cross-linked in an oven, a layer of pressure-sensitive adhesive coating with a thickness of 20 to 70 μm is formed on each side;

[0052] The drying temperature in the oven is set to 90-120°C; the time in the oven is 3-6 minutes.

[0053] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0054] (1) In the present invention, self-synthesized glue is used and rapid viscosity reduction can be achieved by baking at 75°C for 5 minutes; the heat-reducing viscosity-reducing pressure-sensitive adhesive can be recycled after peeling, and different functional monomers are set to produce different overall effects.

[0055] (2) In the present invention, the phase transition of liquid crystal polymer and the decrease in storage modulus of modified polyacrylate under heating conditions are utilized to rapidly reduce the peel strength. When subjected to external force, the component can be separated from the adherend and rework can be achieved. When the temperature returns to room temperature, the liquid crystal polymer returns to its original state, the storage modulus of modified polyacrylate increases, and the peel strength is restored, thereby achieving repeated bonding.

[0056] (3) When reworking, place the parts that need to be reworked or repaired in a heating device (≥70℃) for 5 to 10 minutes, then gently separate the target parts from the adherend, and after returning to room temperature, re-bond the qualified target parts to the adherend with the pressure-sensitive adhesive. During the whole process, there is no debonding or residual adhesive on the heat-reduced adhesive surface, and the parts are not damaged. After returning to room temperature, the pressure-sensitive adhesive can be used for bonding again; the high-adhesive surface maintains stable high adhesion during the heating and cooling process.

[0057] (4) The technical means of the present invention, in terms of thermal viscosity reduction, mainly uses a modified acrylate polymer containing hydroxyl and carboxyl groups in the side chain, and adds a certain amount of liquid crystal polymer modification, and cooperates with epoxy type and isocyanate type curing agents, and a cross-linking reaction occurs after high-temperature baking to form a thermal viscosity reduction pressure-sensitive adhesive. Liquid crystal polymer has a thermal response property, and has excellent mechanical properties of polymer materials at room temperature, and has high fluidity in a liquid crystal state when it is higher than the phase transition temperature; the modified acrylate polymer has a high storage modulus and peel strength at room temperature, and when it reaches above 70°C, the storage modulus and peel strength drop rapidly.

[0058] (5) The technical means of the present invention, in terms of high-viscosity pressure-sensitive adhesive, is mainly based on a high-viscosity polyacrylate polymer containing hydroxyl and carboxyl groups in the side chain, combined with an isocyanate type curing agent, and undergoes a cross-linking reaction after high-temperature baking to form a high-viscosity pressure-sensitive adhesive, which maintains high viscosity at room temperature and 70 to 90°C. DETAILED DESCRIPTION

[0059] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0060] The present invention provides a reworkable heat-reducing adhesive foam tape and a preparation method thereof, and designs several embodiments and comparative examples to conduct performance tests to verify the performance effect of the tape provided by the present invention.

[0061] Example 1

[0062] When preparing the adhesive tape, the following steps are specifically included:

[0063] S1. Preparation of acrylic acid polymers containing amine and carboxyl groups in the side chains;

[0064] The acrylate copolymer was synthesized by solution free radical polymerization. 25 g of hexadecyl acrylate, 35 g of isooctyl acrylate, 18 g of ethyl acrylate, 4 g of acrylic acid, 2.5 g of hydroxyethyl methacrylate and 115 g of ethyl acetate were added to a reaction flask, heated to 65°C, completely dissolved under mechanical stirring at 250 r / min, and nitrogen was passed through for 30 minutes.

[0065] Weigh 0.6 g of initiator azobisisobutyronitrile and dissolve it in 10 g of ethyl acetate, add it dropwise within 3 h using a constant pressure funnel, react at 65 ° C for 7 h, and perform infrared spectroscopy test on the reaction system to observe whether there are characteristic absorption peaks of carbon-carbon double bonds at 1640 cm-1 and 810 cm-1. If not, stop the reaction. If so, add 0.1 g of initiator and continue the reaction until the double bond characteristic peak disappears; an acrylic polymer with amino and carboxyl groups in the side chains is obtained.

[0066] S2. Preparation of liquid crystal polymers;

[0067] Dissolve 65.2g (0.274mol) of 4-(6-hydroxyhexyloxy)benzoic acid in 200mL of N-methylpyrrolidone, put it in an ice-water bath and cool it to 0°C, then start to drop 27.15g (0.3mol) of acryloyl chloride, warm it to room temperature and react for 6h after the dropwise addition is completed, add 400mL of ice water and continue stirring for 1h, then filter it to obtain a white powdery solid, add it to 500mL of 70°C hot water, stir it for 30min, and then filter it to obtain a crude product. The crude product is recrystallized with 150mL of toluene, filtered, and dried in a vacuum oven at 60°C for 12h to obtain 58g of product 3, with a yield of 72.5%;

[0068] Weigh 14.6g (0.05mol) of 4-((6-(acryloyloxy)hexyl)oxy)benzoate, 7.44g (0.06mol) of 2,6-di-tert-butyl-p-cresol, 12.36g (0.06mol) of N,N-dicyclohexylcarbodiimide (DCC) and 200mL of dichloromethane in a 500mL flask, dissolve 1.2g of 4-dimethylaminopyridine (DMAP) in 30mL of dichloromethane, and add dropwise to the reaction flask within 30min using a constant pressure funnel, and react at room temperature for 24h. After the reaction is completed, fully freeze and filter to remove insoluble matter.

[0069] The mixture was then washed with 5 wt% hydrochloric acid solution, 5 wt% NaHCO3 solution and saturated NaCl solution respectively, the insoluble matter was filtered out, and the solvent was removed by rotary evaporation to obtain a crude product. The crude product was recrystallized once with 50 mL of isopropanol and dried in a vacuum oven at 60° C. for 12 h to obtain 12.6 g of a white powdery liquid crystal monomer with a yield of 63.3%.

[0070] Weigh 2 g of the prepared liquid crystal monomer into a 4 mL centrifuge tube, put it into a 60°C water bath to melt the solid monomer into a liquid, add 2 wt% photoinitiator 1173, stir to make it evenly mixed in the liquid crystal monomer, transfer the molten liquid crystal monomer while hot to a curing mold (2×1×0.5 cm) composed of a silicone pad and a glass sheet on a 60°C hot stage, and irradiate it with 365 nm LED ultraviolet light for 1 min with a light intensity of 40 mW / cm2 to obtain the desired liquid crystal polymer.

[0071] S3. Preparation of reworkable heat-reducing foam tape;

[0072] a. Mix 100 parts of an acrylic polymer having an amine group and a carboxyl group in the side chain, 20 parts of a liquid crystal polymer, 0.8 parts of a curing agent, and 40 parts of a solvent, by weight, and perform ultrasonic dispersion to obtain a heat-reduced surface coating mixed solution;

[0073] The acrylic polymer having an amino group and a carboxyl group in the side chain has a glass transition temperature (Tg) of -20°C, a viscosity of 13000 cps / 25°C, and a weight average molecular weight M W The storage modulus G' of the acrylic pressure-sensitive adhesive at 23°C is 280 KPa, and the loss factor tanδ is 1.2; the storage modulus G' of the acrylic pressure-sensitive adhesive at 75°C is 18 KPa, and the loss factor tanδ is 0.01;

[0074] The curing agent is polyisocyanate and epoxy curing agent, with a mass ratio of 1 / 2; the solvent is ethyl acetate.

[0075] b. Mix 100 parts of acrylic polymer containing amine groups in the side chain, 0.4 parts of curing agent and 20 parts of solvent by weight, stir and disperse by ultrasonic to obtain a high-viscosity surface coating mixture.

[0076] The acrylic pressure-sensitive adhesive has a glass transition temperature (Tg) of -10°C and a weight average molecular weight M W The storage modulus G' of the acrylic pressure-sensitive adhesive at 23°C is 260 KPa, and the loss factor tanδ is 1.3; the storage modulus G' of the acrylic pressure-sensitive adhesive at 65°C is 109 KPa, and the loss factor tanδ is 0.9; the storage modulus G' of the acrylic pressure-sensitive adhesive at 75°C is 75 KPa, and the loss factor tanδ is 0.7;

[0077] The curing agent is polyisocyanate; the solvent is ethyl acetate.

[0078] c. Apply the coating mixture described in the above step on the release surface of a release film with a thickness of 70 μm and an aged release force of 52 gf / in, a 24h release force of 45 gf / in, and a residual rate of 85%, and dry at 110°C for 5 minutes to obtain a pressure-sensitive adhesive layer A with a thickness of 50 μm.

[0079] d. Coat the above-mentioned coating mixture on the release surface of a 50 μm thick release film with an aged release force of 28 gf / in, a 24h release force of 13 gf / in, and a residual rate of 86%, and dry at 110°C for 5 minutes to obtain a pressure-sensitive adhesive layer B with a thickness of 50 μm.

[0080] e. Laminating the pressure-sensitive adhesive layer A on the foam substrate to obtain a semi-finished product; laminating the pressure-sensitive adhesive layer B on the other side of the semi-finished product to obtain a reworkable heat-reducing foam tape product, namely, Example 1.

[0081] Example 2

[0082] The specific steps include:

[0083] S1. Preparation of acrylic acid polymers containing amine and carboxyl groups in the side chains;

[0084] The acrylate copolymer was synthesized by solution free radical polymerization. 28 g of hexadecyl acrylate, 32 g of isooctyl acrylate, 19 g of ethyl acrylate, 4 g of acrylic acid, 2.5 g of hydroxyethyl methacrylate and 115 g of ethyl acetate were added to a reaction flask, heated to 65°C, completely dissolved under mechanical stirring at 250 r / min, and nitrogen was passed through for 30 minutes.

[0085] Weigh 0.6 g of initiator azobisisobutyronitrile and dissolve it in 10 g of ethyl acetate, add it dropwise within 3 h using a constant pressure funnel, react at 65 ° C for 7 h, and perform infrared spectroscopy test on the reaction system to observe whether there are characteristic absorption peaks of carbon-carbon double bonds at 1640 cm-1 and 810 cm-1. If not, stop the reaction. If so, add 0.1 g of initiator and continue the reaction until the double bond characteristic peak disappears; an acrylic polymer with amino and carboxyl groups in the side chains is obtained.

[0086] S2. Preparation of liquid crystal polymers;

[0087] Dissolve 65.2g (0.274mol) of 4-(6-hydroxyhexyloxy)benzoic acid in 200mL of N-methylpyrrolidone, put it in an ice-water bath and cool it to 0°C, then start to drop 27.15g (0.3mol) of acryloyl chloride, warm it to room temperature and react for 6h after the dropwise addition is completed, add 400mL of ice water and continue stirring for 1h, then filter it to obtain a white powdery solid, add it to 500mL of 70°C hot water, stir it for 30min, and then filter it to obtain a crude product. The crude product is recrystallized with 150mL of toluene, filtered, and dried in a vacuum oven at 60°C for 12h to obtain 58g of product 3, with a yield of 72.5%;

[0088] Weigh 14.6g (0.05mol) of 4-((6-(acryloyloxy)hexyl)oxy)benzoate, 7.44g (0.06mol) of 2,6-di-tert-butyl-p-cresol, 12.36g (0.06mol) of N,N-dicyclohexylcarbodiimide (DCC) and 200mL of dichloromethane in a 500mL flask, dissolve 1.2g of 4-dimethylaminopyridine (DMAP) in 30mL of dichloromethane, and add dropwise to the reaction flask within 30min using a constant pressure funnel, and react at room temperature for 24h. After the reaction is completed, fully freeze and filter to remove insoluble matter.

[0089] The mixture was then washed with 5 wt% hydrochloric acid solution, 5 wt% NaHCO3 solution and saturated NaCl solution respectively, the insoluble matter was filtered out, and the solvent was removed by rotary evaporation to obtain a crude product. The crude product was recrystallized once with 50 mL of isopropanol and dried in a vacuum oven at 60° C. for 12 h to obtain 12.6 g of a white powdery liquid crystal monomer with a yield of 63.3%.

[0090] Weigh 2 g of the prepared liquid crystal monomer into a 4 mL centrifuge tube, put it into a 60°C water bath to melt the solid monomer into a liquid, add 2 wt% photoinitiator 1173, stir to make it evenly mixed in the liquid crystal monomer, transfer the molten liquid crystal monomer while hot to a curing mold (2×1×0.5 cm) composed of a silicone pad and a glass sheet on a 60°C hot stage, and irradiate it with 365 nm LED ultraviolet light for 1 min with a light intensity of 40 mW / cm2 to obtain the desired liquid crystal polymer.

[0091] S3. Preparation of reworkable heat-reducing foam tape;

[0092] a. Mix 100 parts of an acrylic polymer having an amine group and a carboxyl group in the side chain, 17 parts of a liquid crystal polymer, 0.7 parts of a curing agent, and 40 parts of a solvent, and stir and ultrasonically disperse them to obtain a heat-reduced viscosity surface coating mixed solution;

[0093] The acrylic polymer containing amino groups and carboxyl groups in the side chain has a glass transition temperature (Tg) of -23°C, a viscosity of 12000 cps / 25°C, and a weight average molecular weight M W The storage modulus G' of the acrylic pressure-sensitive adhesive at 23°C is 300KPa, and the loss factor tanδ is 1.4; the storage modulus G' of the acrylic pressure-sensitive adhesive at 75°C is 21KPa, and the loss factor tanδ is 0.02;

[0094] The curing agent is polyisocyanate and epoxy curing agent, with a mass ratio of 1 / 2; the solvent is ethyl acetate.

[0095] b. Mix 100 parts of an acrylic polymer having an amine group in the side chain, 0.5 parts of a curing agent, and 20 parts of a solvent, and stir and ultrasonically disperse them to obtain a high-viscosity surface coating mixture;

[0096] The acrylic pressure-sensitive adhesive has a glass transition temperature (Tg) of -8°C and a weight average molecular weight M W At 760000, the molecular weight distribution is 2.7; the storage modulus G' of the acrylic pressure-sensitive adhesive at 23°C is 300KPa, and the loss factor tanδ is 1.5; the storage modulus G' of the acrylic pressure-sensitive adhesive at 65°C is 113KPa, and the loss factor tanδ is 1.0; the storage modulus G' of the acrylic pressure-sensitive adhesive at 75°C is 81KPa, and the loss factor tanδ is 0.8;

[0097] The curing agent is polyisocyanate; the solvent is ethyl acetate.

[0098] c. Apply the coating mixture described in the above step on the release surface of a release film with a thickness of 70 μm and an aged release force of 52 gf / in, a 24h release force of 45 gf / in, and a residual rate of 85%, and dry at 110°C for 5 minutes to obtain a pressure-sensitive adhesive layer A with a thickness of 45 μm.

[0099] d. Coat the above-mentioned coating mixture on the release surface of a 50 μm thick release film with an aged release force of 28 gf / in, a 24h release force of 13 gf / in, and a residual rate of 86%, and dry at 110°C for 5 minutes to obtain a pressure-sensitive adhesive layer B with a thickness of 45 μm.

[0100] e. Laminating the pressure-sensitive adhesive layer A on the foam substrate to obtain a semi-finished product; laminating the pressure-sensitive adhesive layer B on the other side of the semi-finished product to obtain a reworkable heat-reducing foam tape product, i.e., Example 2.

[0101] Example 3

[0102] A reworkable heat-reducing adhesive foam tape and a preparation method thereof, comprising the following steps:

[0103] S1. Preparation of acrylic acid polymers containing amine and carboxyl groups in the side chains;

[0104] The acrylate copolymer was synthesized by solution free radical polymerization. 22g of hexadecyl acrylate, 38g of isooctyl acrylate, 20g of ethyl acrylate, 4g of acrylic acid, 2.5g of hydroxyethyl methacrylate and 115g of ethyl acetate were added to a reaction flask, heated to 65°C, completely dissolved under mechanical stirring at 250r / min, and nitrogen was passed through for 30 minutes.

[0105] Weigh 0.6 g of initiator azobisisobutyronitrile and dissolve it in 10 g of ethyl acetate, add it dropwise within 3 h using a constant pressure funnel, react at 65 ° C for 7 h, and perform infrared spectroscopy test on the reaction system to observe whether there are characteristic absorption peaks of carbon-carbon double bonds at 1640 cm-1 and 810 cm-1. If not, stop the reaction. If so, add 0.1 g of initiator and continue the reaction until the double bond characteristic peak disappears; an acrylic polymer with amino and carboxyl groups in the side chains is obtained.

[0106] S2. Preparation of liquid crystal polymers;

[0107] Dissolve 65.2g (0.274mol) of 4-(6-hydroxyhexyloxy)benzoic acid in 200mL of N-methylpyrrolidone, put it in an ice-water bath and cool it to 0°C, then start to drop 27.15g (0.3mol) of acryloyl chloride, warm it to room temperature and react for 6h after the dropwise addition is completed, add 400mL of ice water and continue stirring for 1h, then filter it to obtain a white powdery solid, add it to 500mL of 70°C hot water, stir it for 30min, and then filter it to obtain a crude product. The crude product is recrystallized with 150mL of toluene, filtered, and dried in a vacuum oven at 60°C for 12h to obtain 58g of product 3, with a yield of 72.5%;

[0108] Weigh 14.6g (0.05mol) of 4-((6-(acryloyloxy)hexyl)oxy)benzoate, 7.44g (0.06mol) of 2,6-di-tert-butyl-p-cresol, 12.36g (0.06mol) of N,N-dicyclohexylcarbodiimide (DCC) and 200mL of dichloromethane in a 500mL flask, dissolve 1.2g of 4-dimethylaminopyridine (DMAP) in 30mL of dichloromethane, add dropwise to the reaction flask within 30min using a constant pressure funnel, and react at room temperature for 24h. After the reaction is completed, fully freeze and filter to remove insoluble matter. Then wash with 5wt% hydrochloric acid solution, 5wt% NaHCO3 solution, and saturated NaCl solution, filter out the insoluble matter, and remove the solvent by rotary evaporation to obtain a crude product. The crude product was recrystallized once with 50 mL of isopropanol and dried in a vacuum oven at 60° C. for 12 h to obtain 12.6 g of a white powdery liquid crystal monomer with a yield of 63.3%;

[0109] Weigh 2 g of the prepared liquid crystal monomer into a 4 mL centrifuge tube, put it into a 60°C water bath to melt the solid monomer into a liquid, add 2 wt% photoinitiator 1173, stir to make it evenly mixed in the liquid crystal monomer, transfer the molten liquid crystal monomer while hot to a curing mold (2×1×0.5 cm) composed of a silicone pad and a glass sheet on a 60°C hot stage, and irradiate it with 365 nm LED ultraviolet light for 1 min with a light intensity of 40 mW / cm2 to obtain the desired liquid crystal polymer.

[0110] S3. Preparation of a reworkable heat-reducing foam tape;

[0111] a. Mix 100 parts of an acrylic polymer having an amine group and a carboxyl group in the side chain, 15 parts of a liquid crystal polymer, 0.7 parts of a curing agent, and 40 parts of a solvent, by weight, and perform ultrasonic dispersion to obtain a heat-reduced surface coating mixed solution;

[0112] The acrylic polymer containing amino groups and carboxyl groups in the side chain has a glass transition temperature (Tg) of -25°C, a viscosity of 11000 cps / 25°C, and a weight average molecular weight M W The storage modulus G' of the acrylic pressure-sensitive adhesive at 23°C is 320 KPa, and the loss factor tanδ is 1.5; the storage modulus G' of the acrylic pressure-sensitive adhesive at 75°C is 23 KPa, and the loss factor tanδ is 0.02;

[0113] The curing agent is polyisocyanate and epoxy curing agent, with a mass ratio of 1 / 2; the solvent is ethyl acetate.

[0114] b. Mix 100 parts of an acrylic polymer having an amine group in the side chain, 0.6 parts of a curing agent, and 20 parts of a solvent, by weight, and perform ultrasonic dispersion to obtain a high-viscosity surface coating mixed solution;

[0115] The acrylic pressure-sensitive adhesive has a glass transition temperature (Tg) of -7°C and a weight average molecular weight M W The storage modulus G' of the acrylic pressure-sensitive adhesive at 23°C is 315KPa, and the loss factor tanδ is 1.6; the storage modulus G' of the acrylic pressure-sensitive adhesive at 65°C is 116KPa, and the loss factor tanδ is 1.1; the storage modulus G' of the acrylic pressure-sensitive adhesive at 75°C is 84KPa, and the loss factor tanδ is 0.9;

[0116] The curing agent is polyisocyanate; the solvent is ethyl acetate.

[0117] c. Apply the coating mixture described in the above step on the release surface of a release film with a thickness of 50 μm and an aged release force of 28 gf / in, a 24h release force of 13 gf / in, and a residual rate of 85%, and dry at 110°C for 5 minutes to obtain a pressure-sensitive adhesive layer A with a thickness of 40 μm.

[0118] d. Coat the above-mentioned coating mixture on the release surface of a release film with a thickness of 45 μm and an aged release force of 22 gf / in, a 24h release force of 10 gf / in, and a residual rate of 84%, and dry at 110°C for 5 minutes to obtain a pressure-sensitive adhesive layer B with a thickness of 40 μm.

[0119] e. Laminating the pressure-sensitive adhesive layer A on the foam substrate to obtain a semi-finished product; laminating the pressure-sensitive adhesive layer B on the other side of the semi-finished product to obtain a reworkable heat-reducing foam tape.

[0120] Comparative Example 1

[0121] The remaining items of this comparative example refer to Example 1, which is different from Example 1 in that the raw materials for preparing the thermal viscosity-reducing surface glue do not include a curing agent and a liquid crystal polymer, and the other conditions are the same as those in Example 1.

[0122] Comparative Example 2

[0123] The remaining items of this comparative example refer to Example 1, which is different from Example 1 in that the raw materials for preparing the thermal viscosity-reducing surface glue do not include liquid crystal polymer, and the other conditions are the same as those in Example 1.

[0124] Comparative Example 3

[0125] The remaining items of this comparative example refer to Example 1, which is different from Example 1 in that the preparation of the acrylic polymer containing amino and carboxyl groups in the side chain of the raw material for preparing the thermal viscosity-reducing glue is different, and the other conditions are the same as those in Example 1.

[0126] In this comparative example, a solution free radical polymerization method was used to synthesize an acrylate copolymer. 45 g of isooctyl acrylate, 33 g of ethyl acrylate, 4 g of acrylic acid, 2.5 g of hydroxyethyl methacrylate and 115 g of ethyl acetate were added to a reaction flask, the temperature was raised to 65°C, the mixture was completely dissolved under mechanical stirring at 250 r / min, and nitrogen was passed through for 30 minutes.

[0127] Weigh 0.6 g of initiator azobisisobutyronitrile and dissolve it in 10 g of ethyl acetate, add it dropwise within 3 h using a constant pressure funnel, react at 65 ° C for 7 h, and perform infrared spectroscopy test on the reaction system to observe whether there are characteristic absorption peaks of carbon-carbon double bonds at 1640 cm-1 and 810 cm-1. If not, stop the reaction. If so, add 0.1 g of initiator and continue the reaction until the double bond characteristic peak disappears; an acrylic polymer with amino and carboxyl groups in the side chains is obtained.

[0128] Performance Testing

[0129] The room temperature and high temperature peel strength, holding force, and reworkability after heat-removal of the heat-removal adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-3 were tested respectively. The test results are shown in Table 1, wherein the test standards are:

[0130] (1) Initial peeling force from steel plate: The peeling force of the prepared heat-reducing adhesive tape from the steel plate at 180° was tested, referring to the standard GB / T2792;

[0131] (2) Peel strength with steel plate at 75°C, 5 min: After the heat-reducing adhesive tape is attached to the steel plate and left to stand for 20 min, it is placed in a high-temperature oven at 75°C for 5 min and the peel strength is tested;

[0132] (3) Holding force: Tested in accordance with the provisions of GB / T4851;

[0133] (4) Recyclability: The heat-reducing adhesive tape was bonded to a steel plate, peeled off at 75°C, and then bonded to the steel plate and cooled to room temperature (23°C). The initial peeling force of the steel plate was tested. During the entire process, no residual adhesive or debonding occurred, and no foam debris was generated.

[0134] Table 1 Performance test results of various embodiments and comparative examples

[0135]

[0136] It can be seen from Table 1 that the raw material components in the heat-reducing pressure-sensitive adhesive of the present application are reasonably matched to meet the requirements of high viscosity at room temperature, while still maintaining high viscosity at 50°C, ensuring the bonding strength between components, and being able to quickly reduce viscosity and peel off at 75°C. The tape after peeling still has high viscosity at room temperature and can be repeatedly recycled.

[0137] Comparison of Comparative Example 1, Comparative Example 2 and Example 1 shows that without adding a curing agent, the pressure-sensitive adhesive has no viscosity-reducing effect and has low cohesion at room temperature;

[0138] By comparing Comparative Example 2 with Example 1, it is found that without adding liquid crystal polymer, the viscosity reduction effect of the pressure-sensitive adhesive is weak, and the requirement of easy disassembly at high temperature cannot be met;

[0139] By comparing Comparative Example 3 with Example 1, it is found that the absence of long alkyl acrylate in the polymer will result in too low pressure-sensitive adhesive properties under high temperature conditions and low viscosity under normal temperature conditions, which affects actual use.

[0140] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0141] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A reworkable heat-reducing foam tape, comprising a substrate, with pressure-sensitive adhesive layers coated on both sides of the substrate, and a release film attached to the outer side of the pressure-sensitive adhesive layer, characterized in that: The pressure-sensitive adhesive layer includes a high-viscosity pressure-sensitive adhesive and a heat-reduced viscosity pressure-sensitive adhesive; Wherein, the heat-reducing pressure-sensitive adhesive is an acrylic polymer, including the following components by weight: 100 parts of an acrylic acid polymer having an amine group and a carboxyl group in the side chain; 10-30 parts of liquid crystal polymer; Curing agent 0.3-1.2 parts; 30-50 parts of solvent; The acrylic polymer having an amino group and a carboxyl group in the side chain has a glass transition temperature Tg of -15 to -25°C, a viscosity of 10,000 to 15,000 cps / 25°C, and a weight average molecular weight M W 50000~200000, molecular weight distribution is 1.5~3.5; The storage modulus G′ of the acrylic polymer at 23° C. is 200 to 400 KPa, and the loss factor tanδ is 1.0 to 2.0; The storage modulus G' of the acrylic polymer at 75°C is 15-30 KPa, and the loss factor tanδ is 0.01-0.

03.

2. The reworkable heat-reducing foam tape according to claim 1, characterized in that: The acrylic polymer containing amine and carboxyl groups in the side chain includes the following components by weight: 20-30 parts of long alkyl acrylate monomer; 30-40 parts of isooctyl acrylate monomer; 15-20 parts of ethyl acrylate monomer; 0.5-4 parts of hydroxyethyl methacrylate; 1 to 6 parts of acrylic acid; Thermal initiator 0.2-1.0 part; 100-130 parts of solvent; After the above substances are uniformly mixed, a free radical polymerization reaction is carried out at 60-90° C. by slowly dropping the mixed solution step by step for 6-8 hours to obtain an acrylic acid polymer having an amino group and a carboxyl group in the side chain.

3. The reworkable heat-reducing foam tape according to claim 2, characterized in that: The long alkyl acrylate monomer is at least one of hexadecyl acrylate, octadecyl acrylate and behenyl acrylate; the thermal initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, lauroyl peroxide and tert-butyl perbenzoate.

4. The reworkable heat-reducing foam tape according to claim 1, characterized in that: When preparing the liquid crystal polymer, 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoate, 2,6-di-tert-butyl-p-cresol, N,N-dicyclohexylcarbodiimide, dichloromethane, and 4-dimethylaminopyridine are reacted at room temperature for 24 hours; After washing, filtering, rotary evaporation and recrystallization, a liquid crystal monomer, namely 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoate, is obtained; Finally, the liquid crystal monomer is used to obtain a liquid crystal polymer under the irradiation of a photoinitiator and LED ultraviolet light.

5. The reworkable heat-reducing foam tape according to claim 4, characterized in that: The solutions used in the washing process are 5wt% hydrochloric acid solution, 5wt% NaHCO3 solution, and saturated NaCl solution.

6. The reworkable heat-reducing foam tape according to claim 1, characterized in that: The high-viscosity pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive, comprising the following components by weight: 100 parts of an acrylic polymer having an amine group in the side chain; Curing agent 0.2-1 part; 15-30 parts of solvent; The acrylic pressure-sensitive adhesive has a glass transition temperature Tg of -25 to 5°C, a weight average molecular weight MW of 500,000 to 1,000,000, and a molecular weight distribution of 1.5 to 3.2; The storage modulus G′ of the acrylic pressure-sensitive adhesive at 23° C. is 200 to 400 KPa, and the loss factor tanδ is 1.0 to 2.0; The storage modulus G' of the acrylic pressure-sensitive adhesive at 75°C is 60-90 KPa, and the loss factor tanδ is 0.7-0.

9.

7. The reworkable heat-reducing foam tape according to claim 6, characterized in that: The curing agent is at least one of polyisocyanate, epoxy curing agent and metal salt curing agent; the substrate is at least one of polyurethane foam, polyethylene foam and polypropylene foam; The thickness of the substrate is 0.05 to 0.5 mm; The thickness of the pressure-sensitive adhesive layer on both sides of the substrate is 20-70 μm.

8. A reworkable heat-reducing foam tape according to claim 2 or 6, characterized in that: The solvent is at least one of isopropanol, ethyl acetate, toluene and butanone.

9. The reworkable heat-reducing foam tape according to claim 1, characterized in that: The thickness of the release film is 40-80 μm; The release force of the light release surface is 8-15gf / in after 24h, and 20-30gf / in after aging at 70℃ for 20h, and the residual rate is ≥85%; The release force of the heavy release surface after 24 hours is 30-55gf / in, and the release force after aging at 70℃ for 20 hours is 35-70gf / in, and the residual rate is ≥80%.

10. A method for preparing a reworkable heat-reducing adhesive foam tape, for preparing any one of claims 1 to 6 or 9, characterized in that: The coating method used is one of micro-dimpled coating and comma blade coating; The specific operation is as follows: the components of the heat-reducing pressure-sensitive adhesive and the high-viscosity pressure-sensitive adhesive are mixed to prepare a solution, and the dispersion speed is 400-500 rpm / min; The solution is sequentially coated on both sides of the foam substrate, and after being dried, cured and cross-linked in an oven, a layer of pressure-sensitive adhesive coating with a thickness of 20 to 70 μm is formed on each side; The drying temperature in the oven is set to 90-120° C.; the time in the oven is 3-6 minutes.

Citation Information

Patent Citations

  • Reworkable adhesive tape and preparation method thereof

    CN108384471A

  • Thermal viscosity reduction film as well as preparation method and application thereof

    CN113817423A

  • Thermally peelable photocuring pressure-sensitive adhesive doped with thermotropic liquid crystal polymer

    CN113845849A

  • Reversible thermal visbreaking pressure-sensitive adhesive, double-sided adhesive tape and preparation method of reversible thermal visbreaking pressure-sensitive adhesive

    CN117801730A

  • Electrolytic adhesive containing stable polymer and preparation method thereof

    CN118956301A

Cited By

  • Double-sided strong and weak adhesive tape

    CN121203569A